Luciano Curreri and Michel Delville, Il grande ‘Incubo che mi son scelto.’ Prove di avvicinamento a Profondo Rosso (1975-2015) - Pomilio, Daniele (Review of International American Studies, 2017)
Daniele Pomilio University of Udine Italy Luciano Curreri e Michel Delville, Il grande ‘Incubo che mi son scelto.’ Prove di avvicinamento a Profondo Rosso (1975-2015), Piombino, Edizioni Il Foglio, 2015 The text offers a review of Il grande “Incubo che mi son scelto” - a collection of essays written in three different languages by a group of international scholars to celebrate the fortieth anniversary of Profondo Rosso, the cult movie by Dario Argento. The book contributes to the canonization of an Italian classic long neglected by those critics who still consider horror movies a low-rated subgenre comparable to B-movies.